Suicidal Idea Detection on Twitter - Berrios Butron, Juliana (2023)
Sentiment analysis is a new trend' nowadays to understand how people' feel in different situations of their daily life. Social network data is used during the whole process of analysis and' classification, which consists of text data. Using social networks, the emotional level can be monitored or analyzed. In this research work we will classify data from social networks such as twitter regarding suicide and classify it as: active suicidal thinking, passive suicidal thinking, sarcasm related to suicidal thinking, tweets related to suicide (suicide awareness, news, suicide talk) and others.